An overview of biomedical applications of choline geranate (CAGE): a major breakthrough in drug delivery. Issue 40 (13th September 2022) - Riaz, Mubeshar; Akhlaq, Maida; Naz, Sadia; Uroos, Maliha
Abstract : This review summarizes the advancements in the field of biomedical sciences using choline geranate (CAGE) ionic liquid (IL)/deep eutectic solvent (DES) in view of its unique properties. Abstract : A number of studies are on the way to advancing the field of biomedical sciences using ionic liquids (ILs) and deep eutectic solvents (DESs) in view of their unique properties and inherent tunability. These significant solvents tend to enhance the physical properties of the drug, increase their bioavailability and promote the delivery of recalcitrant drugs to the body. One such widely investigated tempting multipurpose IL/DES system is choline geranate (CAGE), which has gained significant interest due to its biocompatible and highly potent antiseptic behavior, which also facilitates its sanitizing ability to combat the coronavirus. This review focuses on total advancements in biomedical applications of CAGE. This biocompatible IL/DES has made facile the solubilization of hydrophobic and hydrophilic drugs and delivery of intractable drugs through physiological barriers by stabilizing proteins and nucleic acids. Therefore, it has been used as a transdermal, subcutaneous, and oral delivery carrier and as an antimicrobial agent to treat infectious diseases and wounds as approved by laboratory and clinical translations. Moreover, current challenges and future outlooks are also highlighted to explore them more purposefully.